Circular economy, marketing and corporate social responsibility: practices of a timber company the contribute to the strengthening of business capacities - Rodríguez Hernández, Reina Helena (2022)
This document, product of the qualitative research process and case study, aims to describe the organizational practices developed by a timber company located near Bogotá (Colombia), its contribution to the industry and the communities, and how these actions incorporate economy circular, marketing and corporate social responsibility for the sustainability. This issue is considered relevant due to the growing criticism surrounding the crisis of natural resources that involves all of humanity and demands actions that contribute to its mitigation, based on the responsible linking of people and organizations. Added to the above is the need to transform the mentality of the human being on the management of solid waste, such as plastic, leading to companies, such as Maderas Cobos, to design new strategies that articulate the circular economy, marketing and social responsibility. Corporate The document incorporates the theories of the three variables addressed and details the strategies that the company develops through collaborative networking, where some of its stakeholders are articulated, such as other companies, suppliers, customers, communities and foundations, integration that contributes to economic production, inclusion from associative work, waste reduction and the promotion of a change of mentality from social marketing that implies commitment of people and companies in the defense of natural resources, and that turn out to be experiences that can be multiplied in other contexts.